CAUSES OF REMANENT MAGNETIZATION IN THE GABBRONORITE OF THE BURAKOVSKIY PLUTON - Sobolev P.O.; Faynberg F.S. (My University, 1990)
The scientific value of rock magnetism and paleomagnetism is difficult to over-estimate, as paleomagnetism is one of the cornerstones of the plate tectonics theory. This field is concerned primarily with the direction of the remanent magnetization vector of rocks, and less often with its magnitude. Recent studies have focused on the correlation of magnetic properties with the composition of magnetic minerals that occur in the rock as independent grains Many investigators have pointed out the important contribution of microscopic ferromagnetic inclusions in silicates to rock magnetism, but there have not yet been any direct demonstrations of this point. The results presented here suggest that the phenomenon is much more widespread in certain rock types.